The World Heritage: Santiago’s Road. (Journal of Parents and Teachers, 2016)
The following article deals with Santiago’s Road such as one of the elements which takes part of the World Heritage. It relates the history and the origins of it related to apostle Santiago. In addition, it refers to pilgrim’s characteristics and elements, who decide to go through that road. Everything offers a full atmosphere of culture and knowledge related to the country’s heritage.
Keywords: education; Santiago’s Road; pilgrim; apostle; history; culture; heritage.